Effects of selenium supplementation on expression of SEPP1 in mRNA and protein levels in subjects with and without metabolic syndrome suffering from coronary artery disease: Selenegene study a double‐blind randomized controlled trial. Issue 10 (22nd June 2018) - Gharipour, Mojgan; Ouguerram, Khadija; Nazih, El‐Hassane; Salehi, Mansour; Behmanesh, Mehrdad; Roohafza, Hamidreza; Hosseini, Syed Mohsen; Nezafati, Pouya; Dianatkhah, Minoo; Gharipour, Amin; Haghjoo, Shaghayegh; Sarrafzadegan, Nizal; et al.
Abstract: Selenoprotein P (SePP) is involved in the protection against diseases. The present study is the first investigation of the effect of selenium supplementation on plasma selenium and expression of SEPP1 in mRNA and protein levels based on metabolic syndrome (MetS), in individuals suffering from coronary artery diseases. In this clinical trial, 160 patients with angiographically documented stenosis of more than 75% in each vessel were enrolled. Patients received either 200‐mg selenium yeast tablets or placebo tablets orally after a meal, once daily for 60 days. The mRNA and protein levels of the selenium and SePP1 products were determined before and after the study. From the initial 160 participants, 145 subjects (71 MetS‐affected individuals, 74 MetS‐unaffected individuals) enrolled in this study. Comparing the selenium and placebo groups, no significant percentage changes of plasma selenium, △Ct SEPP1, or SePP were shown ( P  > 0.05). Moreover, beyond a significant difference for the expression of SePP in the selenium group compared to its baseline level ( P  < 0.05), no other significant differences were revealed for plasma selenium and △Ct SEPP1 after the intervention in either group ( P  > 0.05). Selenium supplementation did not affect plasma selenium or the mRNA or protein level of SePP in either groups after a 2‐months intervention beyond a significant increase of SePP in the MetS group. This trial suggests that further studies should investigate the long‐term use of selenium supplementation and the effect of a SePP increase on MetS as a potential therapeutic effect. Abstract : Selenoprotein P (SePP), a major selenium transport protein, is involved in protection against diseases. This double‐blind randomized controlled trial for the first time investigates the effects of selenium supplementation on plasma selenium and expression of SEPP1 in subjects with and without MetS suffering from coronary artery diseases. In our study, selenium supplementation does not affect plasma selenium, mRNA and protein level of SePP in either of non‐MetS and MetS groups after 2 months intervention besides a significantly increase of SePP in the MetS.